Hubungan antara Peranan Kelompok Tani dengan Pendapatan Petani Bunga Krisan di Desa Pasirlangu Kecamatan Cisarua Kabupaten Bandung Barat - Edeng Edeng; Yayah Haeriah; Asep Najmudin; Wendi Juliawan; Vega Chendra Mulyana (Paspalum: Jurnal Ilmiah Pertanian, 2023)
The purpose of the research was to determine the relationship between the role of farmer groups and the income of chrysanthemum farmers in Pasirlangu Village, Cisarua District, West Bandung Regency. Verification survey research method, sampling was done by simple random sampling method, 20 samples from a population of 36 group members. The relationship between the role of farmer groups and income were analyzed by the Spearman rank test. The results showed that the role of the chrysanthemum farmer group in carrying out its functions as a learning class was included in the medium category, the function as a vehicle for collaboration was included in the medium category, and the function as a production unit was included in the high category, cumulatively included in the high category. Chrysanthemum farming income for farmers who were members of farmer groups in 2023 when used production costs is included in the high category, when farming activities were included in the high category, and when increasing production, it is included in the high category. Cumulatively, it is included in the high category, meaning that the income of chrysanthemum farmers had increased. The relationship between the role of farmer groups and increasing income, in carrying out its function as a learning class and as a vehicle for cooperation, had an insignificant relationship. The role of the group as a production unit had a real (significant) relationship to the income of chrysanthemum farmers in Pasir Langu Village, Cisarua District, West Bandung Regency.